(untitled) (Research, Society and Development, 2021)
Research integrity is a subject of crucial importance when it comes to scientific investigation, and has been receiving more and more attention, both within the Academy and in society in general. In Brazil, for example, criminal legislation protects copyright, defining copyright infringement as crime. Research funding agencies, such as the National Council for Scientific and Technological Development (CNPq) and the São Paulo Research Foundation (FAPESP) have drawn up guides to good practices in research. There are several forms of the so-called scientific misconduct. This may have a larger or smaller scope depending on the region or legislative delimitation considered. This work carried out a survey of international guidelines and national standards on research integrity and scientific misconduct in several countries. It found that, despite established international guidelines, it is clear that the understanding about research integrity principles and what is considered scientific misconduct differ between different (and often neighboring) countries. With research being more and more developed in international cooperation, this can generate different consequences for the same fact, or similar facts – which can be considered as scientific misconduct or disrespect for research integrity in one country and not in another. Or: the applied sanction may be more severe in one place than in another. Furthermore, some researchers, working on the same project, in international cooperation, may be punished in their countries of origin, and others do not. This is a situation of ethical, bioethical and legal questioning that needs answers.